If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + 5) = 28 Reorder the terms: -4(5 + x) = 28 (5 * -4 + x * -4) = 28 (-20 + -4x) = 28 Solving -20 + -4x = 28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + -4x = 28 + 20 Combine like terms: -20 + 20 = 0 0 + -4x = 28 + 20 -4x = 28 + 20 Combine like terms: 28 + 20 = 48 -4x = 48 Divide each side by '-4'. x = -12 Simplifying x = -12
| 0-5=6-7x | | 0-5x=-7x | | -48=6(a-1) | | x+2x+x+25=165 | | 4+7x=34-x | | -57=-5x+8(3+4x) | | 5+8m=-1+5m | | 6x-5=4x-53 | | y=.666x-1 | | 6x-4x+7=0 | | 4x-2(x+3)=3x | | 63=-7(3n-3) | | X=-3.6X^2-8.8X+8.3 | | 6x-3(4+x)=0 | | 4x=-25 | | 47533.32=2*3.14*r^2+2*3.14*r*232 | | f/5+4=29 | | -2(9-3x)+2=-4 | | -73=6m-5(m-3) | | 7-3(2-x)+6=-2 | | 72*64-7/80+4*x=40*52*2 | | -6(x-3)-8=-8 | | 3265+28=oshawn | | 4=4a-8(a-2) | | -8+3(x-6)=1 | | -9(x+4)=18 | | 6(-3-x)+8=-16 | | 4(-x+4)+6=2 | | 20=6(2+x)+8 | | 743-28=x | | 4-3(2-2x)=4 | | x(x-2)(x+3)=0 |